A brief history of Massospondylus: its discovery, historical taxonomy and redescription of the original syntype series - Barrett, Paul M; Chapelle, Kimberley EJ (The Evolutionary Studies Institute, 2024)
Massospondylus carinatus Owen, 1854 is one of the first dinosaurs to have been described from outside Europe and was based on material collected from what is now the upper Elliot Formation of the Free State province, South Africa. The species was included in various taxonomic reviews during the late nineteenth and early twentieth centuries but no additional material was referred beyond the original syntype series and it remained poorly known. This was exacerbated by the destruction of the syntypes during World War II. From the 1970s onward, fieldwork in the upper Stormberg Group of South Africa, Lesotho and Zimbabwe led to the discovery of many new sauropodomorph dinosaur specimens that have been referred to the taxon (often uncritically) that have been used to shed further light on the anatomy, palaeobiology and biostratigraphical utility of Massospondylus carinatus. Here, we review the taxonomic history of this species, provide updated descriptions of the syntypes (based on surviving casts) and use apomorphies to identify these specimens more accurately.
Keywords: Massospondylus carinatus, Dinosauria, Sauropodomorpha, Orpen Collection, upper Elliot Formation, historical taxonomy.; SDG-15: Life on land